PASTORAL PENGATURAN KEHAMILAN SETURUT AJARAN MORAL GEREJA KATOLIK - Antonius Virdei Eresto Gaudiawan (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Magisterium of the Church has established sexual ethics for a long time ago. Church resists artificial birth control that morally are contraceptive and abortive. Church gives guidance for Christian to use natural birth control recognized as a gift of God. Nevertheless, many Christian have used artificial birth control. Some researches affirmed this judgment. Thereof, the Church has to continuously invite Christian couples for using natural birth control throughout their life. Church has to establish such a natural birth control centre for on going education both related to sexual ethics and the convince of the Christian couples effectively practicing natural birth control.